PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ICT PADA PEMBELAJARAN IPA MATERIKONDUKTOR DAN ISOLATOR KELAS IV SDN 057205 STABAT LAMA - Desy Crismas Silaban (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this article is to give little thought to the development of the science-based information communication and technology (ict) medium learning. The article is based on library studies to describe the science-based information communication and technology (ict) learning media. The learning media is a component in the learning process. The creative use of the learning media can increase the effectiveness and efficiency of learning so that the purpose of learning can be accomplished. The method of research used in experimental methods with research design, including true coordinates. The use of ict learning media will increase the motivation for students' study. Administrative research USES test instruments either prestes and postes on the subject science materials conductors and insulators. Descriptive analysis results in average pretes and postes 53.76 and 79.14. Gain average value shows 0.55 to moderate category.Â Keywords:Â Learning Medium, Result of Learning, Â Information Communication and Technology (ICT)Â